Implications of product architecture on marketing strategy - Kua, Chin Hock (2014)
Today's dynamic market environment is marked by rapid introduction of products with innovative functions and large product variety. In this light, the report studies the implications of proposed product architecture on marketing strategy. The study of trade customer needs reveal that the trade is more concerned about business issues rather than product issues. The business issues are dominated by profit margin, turnover rate, product variety and price. Although a large product variety is desirable, yet the product "iron" offers limited opportunities for customization. This limited scope is dominated by a greater desire of customization on hard features rather than on soft features. In customization scenario, to ascertain the profitability, a cost model is developed which addresses two products belonging to a product family at the same time, so that leverage can be gained from the shared costs. A Linear Programming model is developed which proposes an optimum product-mix, where minimizing the costs associated with the unutilized capacity of the tools is the primary objective.